2016
DOI: 10.1002/2015jc011504
|View full text |Cite
|
Sign up to set email alerts
|

Timing and regional patterns of snowmelt on Antarctic sea ice from passive microwave satellite observations

Abstract: An improved understanding of the temporal variability and the spatial distribution of snowmelt on Antarctic sea ice is crucial to better quantify atmosphere-ice-ocean interactions, in particular sea-ice mass and energy budgets. It is therefore important to understand the mechanisms that drive snowmelt, both at different times of the year and in different regions around Antarctica. In this study, we combine diurnal brightness temperature differences (dT B (37 GHz)) and ratios (T B (19 GHz)/T B (37 GHz)) to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 52 publications
(81 reference statements)
5
49
0
1
Order By: Relevance
“…Consequently, the strong temperature gradients required for constructive metamorphism and the subsequent formation of faceted and depth hoar grains are intermittently interrupted (e.g., Colbeck, 1982). Instead, thaw-refreezing events might have developed the pronounced melt-freeze forms in the MYS during the previous spring-summer transition, which is supported by observation of multiple basal and internal thaw-refreezing events by satellite microwave observations in the area (Arndt et al, 2016;Willmes et al, 2006). In contrast, FYS is dominated by snow accumulation (wind slab) and fragmented grains, the prestate of depth hoar, dominated.…”
Section: Variability Of Snow Properties In Different Snow Regimesmentioning
confidence: 91%
See 2 more Smart Citations
“…Consequently, the strong temperature gradients required for constructive metamorphism and the subsequent formation of faceted and depth hoar grains are intermittently interrupted (e.g., Colbeck, 1982). Instead, thaw-refreezing events might have developed the pronounced melt-freeze forms in the MYS during the previous spring-summer transition, which is supported by observation of multiple basal and internal thaw-refreezing events by satellite microwave observations in the area (Arndt et al, 2016;Willmes et al, 2006). In contrast, FYS is dominated by snow accumulation (wind slab) and fragmented grains, the prestate of depth hoar, dominated.…”
Section: Variability Of Snow Properties In Different Snow Regimesmentioning
confidence: 91%
“…Furthermore, following our assumption that the density can be neglected for the variability analysis, an overall higher property variability is evident for MYS than for FYS. This might be attributed to diurnal thaw-freeze cycles in the upper snowpack as well as internal melt events in the previous summer in the area observed in a field studies on snow properties during the spring-summer transition by, for example, Nicolaus et al (2009) as well as identified by Arndt et al (2016) from passive microwave observations. In contrast, FYS is expected to be more homogenous.…”
Section: Variability Of Snow Properties In Different Snow Regimesmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition to being younger, thinner and more dynamic, the Antarctic snow-sea ice system is also characterized by highly-variable meteorological conditions 10 in which heavy snowfall and synoptically-driven thaw events occur year-round 27,67 . The combined effect of heavy snowfall and thinner ice results in widespread flooding and snow-ice formation (Fig.…”
Section: Snow On Antarctic Sea Icementioning
confidence: 99%
“…The results from nonflooded grid cells show high extinction coefficients for snow (31.76 ± 0.69 m −1 , section 3.3) revealing a strong scattering in the respective snowpack. Since Antarctic sea ice is covered with snow during most of the year [ Massom et al ., ], seasonal snowmelt processes [ Arndt et al ., ] lead to a snowpack consisting of highly compacted and metamorphic layers of snow with internal ice layers [ Nicolaus et al ., ]. This highly inhomogeneous snowpack and density structure leads to weak observed correlations of transmitted solar radiation with snow depth (Figure ).…”
Section: Discussionmentioning
confidence: 99%